Role of macrophage polarization in heart failure and traditional Chinese medicine treatment - Zhu, Zheqin; Wang, Min; Lu, Shenghua; Dai, Sisi; Liu, Jianhe (Frontiers in Pharmacology, 2024)
Heart failure (HF) has a severe impact on public health development due to high morbidity and mortality and is associated with imbalances in cardiac immunoregulation. Macrophages, a major cell population involved in cardiac immune response and inflammation, are highly heterogeneous and polarized into M1 and M2 types depending on the microenvironment. M1 macrophage releases inflammatory factors and chemokines to activate the immune response and remove harmful substances, while M2 macrophage releases anti-inflammatory factors to inhibit the overactive immune response and promote tissue repair. M1 and M2 restrict each other to maintain cardiac homeostasis. The dynamic balance of M1 and M2 is closely related to the Traditional Chinese Medicine (TCM) yin-yang theory, and the imbalance of yin and yang will result in a pathological state of the organism. Studies have confirmed that TCM produces positive effects on HF by regulating macrophage polarization. This review describes the critical role of macrophage polarization in inflammation, fibrosis, angiogenesis and electrophysiology in the course of HF, as well as the potential mechanism of TCM regulation of macrophage polarization in preventing and treating HF, thereby providing new ideas for clinical treatment and scientific research design of HF.